A study on the effectiveness of waste management in Malaysia / Hanni Najla Yusuf and Nur Hanisah Khalid - Yusuf, Hanni Najla; Khalid, Nur Hanisah (2022)
The study’s goal was to investigate the and determine the relationship of the effectiveness of waste management among the public in Malaysia between public awareness and education, public participation, and roles of government. The study also investigated the satisfaction level of the effectiveness of waste management in the neighbourhood among the public Malaysian. The research was carried out from April of 2022 to July of 2022. This study adopted the convenience sampling and questionnaires in collecting the data. This study will be conducted among the Malaysian public to determine the effectiveness of waste management. The purpose of this study is to find out the factors that contribute to the effectiveness of waste management as solid waste management is considered the biggest challenge Malaysia has to face. The result from this study is that the Malaysian public is aware of waste management. There is a significant relationship between effectiveness of waste management and public education and awareness, public participation, as well as roles of the government in Malaysia. This study’s findings could be used as a reference for improving current policy in order to enable its efficiency in the present and future.